2018
DOI: 10.1136/neurintsurg-2018-014128
|View full text |Cite
|
Sign up to set email alerts
|

Y-configuration stenting for coiling of wide-neck bifurcation aneurysms using Low-profile Visualized Intraluminal Support Junior

Abstract: LVIS Jr Y-stenting and coiling for wide-neck bifurcation aneurysms seems to be feasible with acceptable safety and to provide durable aneurysm occlusion for wide-neck bifurcation aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Despite the fact that our cohort consisted only of MCA aneurysms, which are considered technically challenging to treat by the endovascular approach, we achieved high immediate and long-term total occlusion rates, which are similar to, if not better than, those of other published LVIS Jr. series [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Follow-up imaging showed complete or near-complete aneurysm occlusion in 92% of the cases.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Despite the fact that our cohort consisted only of MCA aneurysms, which are considered technically challenging to treat by the endovascular approach, we achieved high immediate and long-term total occlusion rates, which are similar to, if not better than, those of other published LVIS Jr. series [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Follow-up imaging showed complete or near-complete aneurysm occlusion in 92% of the cases.…”
Section: Discussionsupporting
confidence: 61%
“…High technical success rate (95%) was observed in our study, which is similar to previous papers. The reported rate of occurrence of in-stent thrombosis is variable in the literature [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. In another large series of aneurysms treated with the assistance of the LVIS Jr. by Shankar et al, it was observed in 14% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 But as with the previous work of Park et al, Sanmaniego et al and Conrad et al, we enjoyed a high technical success rate with a single instance of asymptomatic in stent stenosis and no cases of stent migration. 21,22,24 We have found that the ability to compress the braided stent during deployment can greatly aid in its outward expansion and in the vast majority of cases relieves any poor opening that may be seen during deployment. In addition, the ability to recapture the LVIS Jr at up to 80% deployment gives a level of control and comfort, in case of poorly witnessed opening.…”
Section: Discussionmentioning
confidence: 99%
“…7,[15][16][17][18][19][20] At least six case series have specifically looked at Y-stent or other multistent constructs with braided stents. 6,14,[21][22][23][24] Three of these series specifically limited themselves to aneurysms treated with Y-stent LVIS Jr constructs. 21,22,24 However, one of these case series included only two cases, and the number of reported cases of aneurysms treated with LVIS Jr Y-stent constructs remains low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation